Phytochemicals mediated modulation of micrornas and long non-coding rnas in cancer prevention and therapy - Ruiz-Manriquez, Luis M.; Estrada-Meza, Carolina; Benavides-Aguilar, Javier A.; Ledesma-Pacheco, S. Janin; Torres-Copado, Andrea; Serrano-Cano, Francisco I.; Bandyopadhyay, Anindya; Pathak, Surajit; Chakraborty, Samik; Srivastava, Aashish; Sharma, Ashutosh; Paul, Sujay (Wiley, 2022)
MicroRNAs (miRNAs) and long noncoding RNAs (lncRNAs) are two main categories of noncoding RNAs (ncRNAs) that can influence essential biological functions in various ways, as well as their expression and function are tightly regulated in physiological homeostasis. Additionally, the dysregulation of these ncRNAs seems to be crucial to the pathogenesis of human diseases. The latest findings indicate that ncRNAs execute vital roles in cancer initiation and progression, and the cancer phenotype can be reversed by modulating their expression. Available scientific discoveries suggest that phytochemicals such as polyphenols, alkaloids, terpenoids, and organosulfur compounds can significantly modulate multiple cancer‐associated miRNAs and lncRNAs, thereby inhibiting cancer initiation and development. However, despite promising outcomes of experimental research, only a few clinical trials are currently being conducted to evaluate the therapeutic effectiveness of these compounds. Nevertheless, understanding phytochemical‐mediated ncRNA regulation in cancer and the underlying molecular mechanisms on tumor pathophysiology can aid in the development of novel therapeutic strategies to combat this deadly disease.